Survival Analysis of Trabeculectomy and Phacotrabeculectomy in Primary Angle Closure Glaucoma (Majalah Kedokteran Bandung, 2024)
Glaucoma is the global leading cause of irreversible blindness. Primary angle closure glaucoma occurs most frequently in Asian populations, including in Indonesian population. Surgical management of Primary Angle Closure Glaucoma (PACG) includes cataract extraction, trabeculectomy, or combined phacotrabeculectomy. Many patients presented in the advanced stages of the disease with significant cataracts, requiring combined surgery. This study aimed to determine whether trabeculectomy alone was better in reducing intraocular pressure compared to phacotrabeculectomy in primary angle closure glaucoma. This was an analytic retrospective observational study reviewing medical records of  PACG patients underwent trabeculectomy or phacotrabeculectomy from January to December 2015, within a 5-year follow-up period of a tertiary eye hospital. The success rates of the two groups were assessed with Kaplan-Meier survival analysis. Success criteria were defined as > 20% reduction of IOP or  IOP
Keywords: Intraocular pressure; phacotrabeculectomy; survival analysis; trabeculectomy